PULMONARY REHABILITATION POST-COVID-19: STRATEGIES FOR FUNCTIONAL RECOVERY AND REDUCTION OF READMISSIONS - Martins, Poliana Barros (LUMEN ET VIRTUS, 2024)
The COVID-19 pandemic has resulted in a substantial population with persistent respiratory sequelae requiring effective rehabilitation strategies. Pulmonary rehabilitation (PR) involving respiratory techniques and early mobilization has emerged as a critical approach to support functional recovery and reduce hospital readmissions in patients recovering from COVID-19-related pulmonary complications. This article reviews current evidence on the evaluation of respiratory techniques and the role of early mobilization in the rehabilitation of post-COVID-19 patients, highlighting improvements in exercise capacity, lung function, dyspnea perception, and quality of life.